2000
DOI: 10.1159/000012839
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of n–3 Polyunsaturated Fatty Acids (PUFA) in Foods Enriched with Microencapsulated Fish Oil

Abstract: Objective: Incorporation of fish oil into food products provides a means of increasing n–3 fatty acid intake, particularly in populations where fish consumption remains low. The aim of the present study was to evaluate the bioavailability of n–3 PUFA in microencapsulated fish-oil-enriched foods compared with an equal amount of n–3 PUFAs contained in fish oil capsules. Methods: Twenty-five healthy female volunteers were randomly assigned to one of two groups for the 4-week intervention: one group received 0.9 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 11 publications
1
53
1
3
Order By: Relevance
“…When 500 ml/day of fish oil fortified, partially fat reduced milk, also providing 300 mg EPA þ DHA daily, was consumed for 6 weeks, plasma phospholipid EPA and DHA both increased by 31% (Visioli et al, 2000). Wallace et al (2000) used microencapsulated fish oil incorporated into bread, biscuits and soup to achieve a daily intake of 900 mg of LC n-3 PUFA/day, and reported that subjects expressed a preference for the bread as it was easier to incorporate into the normal diet. Increases in platelet EPA and DHA of 82 and 44%, respectively, were observed after 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…When 500 ml/day of fish oil fortified, partially fat reduced milk, also providing 300 mg EPA þ DHA daily, was consumed for 6 weeks, plasma phospholipid EPA and DHA both increased by 31% (Visioli et al, 2000). Wallace et al (2000) used microencapsulated fish oil incorporated into bread, biscuits and soup to achieve a daily intake of 900 mg of LC n-3 PUFA/day, and reported that subjects expressed a preference for the bread as it was easier to incorporate into the normal diet. Increases in platelet EPA and DHA of 82 and 44%, respectively, were observed after 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, DHA-MG produces a better increase in plasma and erythrocyte DHA than DHA-EE. The reduction of AA observed in group DHA-MG, not observed in group DHA-EE, may be due to the competition of DHA (at the sn-2 position) to substitute the same position occupied by AA in plasma triacylglycerides and erythrocyte membrane phospholipids [16] . The reduction in EPA content observed in both experimental groups should be also ascribed to the same competition of DHA and EPA.…”
Section: Discussionmentioning
confidence: 73%
“…Certaines nanoparticules (NLC pour « nanostructured lipid carrier ») sont produites a partir d'un m elange de lipides solides et liquides (Muchow et al, 2008 ;Muller et Keck, 2004 ;Shidhaye et al, 2008). L'ensemble de ces nanoparticules lipidiques ont et e utilis ees pour am eliorer la biodisponibilit e orale de micronutriments comme des vitamines liposolubles (Iscan et al, 2005 ;Pople et Singh, 2006) et des om ega-3 (Muchow et al, 2009 ;Wallace et al, 2000) ainsi que des mol ecules th erapeutiques comme le paclitaxel (Peltier et al, 2006), l'ibuprof ene (Lamprecht et al, 2004) et l'insuline (Sarmento et al, 2007).…”
Section: Propri Et Es Thermiques Et Polymorphisme D'huiles Et Graisseunclassified